Conducting LaVO3/SrTiO3 Interface: Is Cationic Stoichiometry Mandatory?. Issue 6 (20th November 2019) - Tomar, Ruchi; Varma, Rahul Mahavir; Kumar, Nand; Sarma, D. D.; Maryenko, Denis; Chakraverty, Suvankar
Abstract: The origin of the conductivity at the interface of two insulating perovskite oxides is a matter of intensive studies. The conductivity generated at the interface of insulating LaVO3 (LVO) and SrTiO3 (STO) is explained in terms of polar catastrophe. Here, the authors grown LVO films on (001) TiO2 ‐terminated STO substrate employing pulsed laser deposition technique and demonstrate a transition from conducting to insulating interface by changing the La‐stoichiometry by only 1%, whereby such transition takes place for La‐deficient films. The effect of cation (non)stoichiometry of LVO film on both carrier density and mobility is studied and compared with previously reported LaAlO3 –STO interface. This observation suggests a revisit to the explanation of possible origin of such conductivity beyond the polar catastrophe scenario and can be instrumental in search for novel conducting interfaces. Abstract : The LaVO3 /SrTiO3 heterostructure demonstrates a transition from conducting to insulating interface by changing the La‐stoichiometry by only 1%. The La‐deficient films show metallic behavior whereas stoichiometric as well as La‐rich films remain insulating. The cationic stoichiometry in LaVO3 films grown on (001) TiO2 ‐terminated SrTiO3 employing pulsed laser deposition technique, varies on changing the ablating laser fluence.